A rare case of repeated expulsions of a giant cervical fibroid per vaginum followed by delivery of near term babies in two consecutive pregnancies - Kanti, Vaibhav; Mishra, Pragati; Gupta, Vandana; Vishwakarma, Soniya; Kumari, Kalpana; Pandey, Pinki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Huge cervical fibroid polyp with red degeneration, obstructing birth canal might be a night mare for obstetricians. Most of us will plan for a caesarean section but somehow due to lack medical consultation; a patient in rural setup with a huge cervical fibroid, delivered normal in two consecutive pregnancies. This case is unique because no such case has been reported in literature where normal delivery took place twice in the same patient, with such a huge fibroid with red degeneration, obstructing the birth canal.